2020
DOI: 10.3389/fcell.2020.00660
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Proteome of Affected Glutamatergic Neurons in a Mouse Model of Leigh Syndrome

Abstract: Defects in mitochondrial function lead to severe neuromuscular orphan pathologies known as mitochondrial disease. Among them, Leigh Syndrome is the most common pediatric presentation, characterized by symmetrical brain lesions, hypotonia, motor and respiratory deficits, and premature death. Mitochondrial diseases are characterized by a marked anatomical and cellular specificity. However, the molecular determinants for this susceptibility are currently unknown, hindering the efforts to find an effective treatme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Remarkably, absence of the NDUFS4 protein induced near complete absence of the NDUFA12 subunit and increased the protein level of NDUFA2 (an assembly factor of CI) in brain, liver, heart, kidney, diaphragm and skeletal muscle of Ndufs4 −/− -WB animals. 64 This finding was confirmed in Ndufs4 −/− -WB-derived mouse embryonic fibroblasts (MEFs; see below), Ndufs4 −/− brainstem glutamatergic neurons 94 and NDUFS4 -mutated Leigh syndrome patient cells. Compatible with previous data, 91 Ndufs4 −/− -WB-derived MEFs displayed in situ CI activity, but BN–PAGE analysis revealed that NDUFAF2 attached to an inactive CI subcomplex (CI-830) and inactive assemblies of higher molecular weight.…”
Section: The Ndufs4 Whole-body Knockout Mouse Modelmentioning
confidence: 78%
“…Remarkably, absence of the NDUFS4 protein induced near complete absence of the NDUFA12 subunit and increased the protein level of NDUFA2 (an assembly factor of CI) in brain, liver, heart, kidney, diaphragm and skeletal muscle of Ndufs4 −/− -WB animals. 64 This finding was confirmed in Ndufs4 −/− -WB-derived mouse embryonic fibroblasts (MEFs; see below), Ndufs4 −/− brainstem glutamatergic neurons 94 and NDUFS4 -mutated Leigh syndrome patient cells. Compatible with previous data, 91 Ndufs4 −/− -WB-derived MEFs displayed in situ CI activity, but BN–PAGE analysis revealed that NDUFAF2 attached to an inactive CI subcomplex (CI-830) and inactive assemblies of higher molecular weight.…”
Section: The Ndufs4 Whole-body Knockout Mouse Modelmentioning
confidence: 78%
“…Peptides were analyzed using an Orbitrap Fusion Lumos Tribrid mass spectrometer coupled to a Thermo Scientific Dionex Ultimate 3000 ultrahigh‐pressure chromatographic system (Thermo Fisher Scientific) as described previously [17].…”
Section: Methodsmentioning
confidence: 99%
“…Peptide alignment and protein sequence analyses from the fragmentation spectra were performed using the Bruker Daltonics software and Mascot search engine, with incorporation of the EDMAN degradation data. LC.ESI-MS/MS analysis were performed in an Orbitrap Fusion Lumos Tribid spectrometer (Thermo Fisher Scientific, Waltham, MA, USA), using a μ-precolumn Acclaim C18 PepMap100 and a C18 Acclaim PepMap RSLC (nanoViper, Waltham, MA, USA) analytical column, following the details reported in [ 44 ]. Validation of the final derived sequence was achieved by high resolution/high accuracy MALDI.MS analysis on a Bruker timsTOF fleX mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%